PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE SYNERGETIC TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 BATANG ANAI KABUPATEN PADANG PARIAMAN - ALMI, ROBI; Delsi K, Delsi K; Rahima, Rahima (STKIP PGRI Sumbar, 2014)
ABSTRACT Background of this research are the student disable to share their knowledge with their friends in the classroom, and the students understanding of mathematical concepts are still low, the solution is the researcher try to apply an active learning strategy tipe synergetic teaching. This study aims to determine whether students understanding of mathematical concepts by using active learning strategies synergetic type of teaching better than students understanding of mathematical concepts with conventional learning of the eight grade students at SMPN 2 Batang Anai Academic Year 2013/2014. This research is an experimental study with random trials on the subject. The population in this study were students of the eight grade at SMPN 2 Batang Anai. Based on the analysis of data obtained P-value = 0,039 was smaller than α = 0,05 then reject H0, so the research hypothesis was accepted. It can be concluded that the students understanding of mathematical concepts by applying active learning strategies synergetic type of teaching better than students understanding of mathematical concepts with conventional learning of the eight grade students at SMPN 2Batang Anai Academic year 2013/2014.